Selection of microorganisms resistant to the effluent discharged in a landfarming in the city of San Luis - Salinas, Adrian (2024)
Biodegradation carried out by indigenous microorganisms is one of the main mechanisms by which different contaminants can be naturally eliminated from the environment. The success of a bioremediation process depends on the intrinsic capacity of the system to trigger and maintain conditions that promote the contaminants biodegradation at high rate. The objective of this work was to study the microorganism’s resistance capacity to resin effluents for their use in the bioaugmentation process. The isolated microorganisms from landfarming, in previous works, were seeded in solid Eg medium (g L-1: glucose, 10; K2HPO4, 0.125; KH2PO4, 0.125; MgSO4, 0.1 y yeast extract,1; agar 15) pH 6,0± 0,2, incubated until growth at 29°C. A central channel was made in each plate in which the effluent diluted to 50% was added. On the other hand, the inhibition effect between the different strains of bacteria and fungi was tested. And finally, a quantitative test was carried out in 10 mL of LB glu liquid medium (g L-1: glucose, yeast extract, peptone, sodium chloride) at different concentrations of the resin effluent (25%, 50% and 75%) at 150 rpm to analyse the individual resistance of the microorganisms to the effluent. Culture medium and water were used as reference. From these tests, four resistant microorganisms (bacteria and fungi) were obtained, which did not show inhibition among themselves. Furthermore, growth of the microorganisms could be visualized at all effluent concentrations tested, being faster and greater at highest concentrations of effluent. The latter, shows that microorganisms use the effluent as a source of carbon and energy for its growth. These preliminary results show that landfarming has an active microbiota and it is feasible to isolate microorganisms that can be used in bioaugmentation processes with native strains.